The determinants of the prevalence of single mothers: A cross-country analysis - Libertad González (Luxembourg Income Study (LIS), 2005)
This paper examines the effect of public assistance, labor market and marriage market conditions on the prevalence of single mother families across countries and over time. A multinomial logit derived from a random utility approach is estimated using individual level data for 14 countries. I find evidence that increases in the level of public support are significantly and positively associated with a higher incidence of both never married and divorced mothers. The results also suggest that single mothers are more prevalent when female wages are lower. Higher male earnings and employment opportunities in a woman's marriage market appear to lead to fewer never married mothers, but more divorced mothers. Higher child support or alimony payments are associated with a higher prevalence of divorced mothers.
Keywords: J12; J13; I38; 330; single mothers; marriage; fertility; welfare benefits; marriage markets; Alleinerziehende; Familienökonomik; Arbeitsmarkt; Familienleistungsausgleich; Welt